A survey to explore the psychological impact of the COVID‐19 pandemic on radiation therapists in Norway and Canada: A tale of two countries. Issue 4 (29th October 2021) - Morassaei, Sara; Di Prospero, Lisa; Ringdalen, Elisabeth; Olsen, Sunniva S.; Korsell, Agnethe; Erler, Darby; Ying, Carmen; Ho Choi, Sang; Bolderston, Amanda; Middleton, Jacqueline; Johansen, Safora
Abstract: Introduction: Several studies have demonstrated the psychological impact of the COVID‐19 pandemic on health care providers. However, there is little known about how the COVID‐19 pandemic has impacted radiation therapists (RTs) in Norway or Canada. The aim of this investigation was to study the psychological impact of working during the COVID‐19 pandemic among RTs in Canada and Norway. Methods: Online surveys were administered to a convenience sample of RTs and RT department managers. Approximately 2000 and 300 RTs were invited to participate from Canada and Norway, respectively. The RT survey collected information on demographics, work‐related stressors, psychological impact, quality of life, and workplace support programmes. The RT manager survey collected information on departmental changes, patient volumes, staff shortages and redeployment, personal protective equipment, and infection control measures. Descriptive analysis, group comparisons and logistic regression were used to examine the impact of COVID‐19 on RTs in the two countries, while open‐ended questions were examined through thematic analysis. Results: Work‐related stress and anxiety were prevalent among Canadian ( n = 155) and Norwegian RTs ( n = 124), with Canadian RTs reporting higher levels. Fear of transmission, changes in PPE usage, and changes in staffing were reported as the most frequent work‐related stressors. Themes related to working during the pandemic included: generalised anxiety; physical, emotional and cognitive symptoms of stress; and loneliness, as well as negative impact on health and quality of relationships. Survey findings from RT department managers in Canada ( n = 12) and Norway ( n = 13) suggest that the pandemic had an organisational impact on RT departments due to implemented infection control measures and changes in staffing. Conclusion: The COVID‐19 pandemic has led to similar stressors amongst Canadian and Norwegian RTs but relatively higher levels of psychological impact among Canadian RTs. Findings demonstrate the importance of mental health support programmes in the workplace to mitigate the psychological impact of the COVID‐19 pandemic on RTs. Abstract : The overall aim of this investigation was to study the psychological impact of working during the COVID‐19 pandemic among RTs in Canada and Norway. Work‐related stress and anxiety were prevalent among Canadian and Norwegian RTs, with Canadian RTs reporting higher levels. Fear of transmission, changes in PPE usage, and changes in staffing were reported as the most frequent work‐related stressors. The findings suggest that the COVID‐19 pandemic has led to similar stressors amongst Canadian and Norwegian RTs but relatively higher levels of psychological impact among Canadian RTs.